Labour market flows: Facts from the United Kingdom - Pedro Gomes (Institute for the Study of Labor (IZA), 2010)
This paper documents a number of facts about worker gross flows in the United Kingdom for the period between 1993 and 2010. Using Labour Force Survey data, I examine the size and cyclicality of the flows and transition probabilities between employment, unemployment and inactivity, from several angles. I examine aggregate conditional transition probabilities, job-to-job flows, employment separations by reason, flows between inactivity and the labour force and flows by education. I decompose contributions of job-finding and job-separation rates to fluctuations in the unemployment rate. Over the past cycle, the job-separation rate has been as relevant as the job-finding rate.
Keywords: E24; J60; 330; worker gross flows; job-finding rate; job-separation rate; transition probabilities